GIS based methodology to analyse the public transport supply – Hungarian case studies - Bárta, Martin (Geographica Pannonica, 2022)
The paper aims to introduce a new way of comparing the efficiency of public transport operations based on publicly available data. It draws on four main sources, the Hungarian Central Statistical Office, public transport provider data, GTFS and OSM map layers. Methodologically, it combines the use of the GTFS format and corresponding static timetable component files, Thiessen polygons and empirical selection of relative indicators. As places of research, three comparable Hungarian cities have been selected by their population size; Pécs, Szeged and Miskolc. The comparison consists of 8 quantitative indicators that cover six major geographical aspects of transport operation (accessibility in terms of proximity, capacity, connectivity, density, frequency and velocity of vehicles). The analysis does not consider the mode of public transport, thus opening up the possibility of an independent comparison of efficiency regardless of various infrastructure characteristics. The results show that Miskolc and Pécs achieved the best values in four indicators. On the contrary, the city of Szeged, despite its diverse structure of transport modes, does not have an advantage in any aspect. The relatively loosely anchored methodology leaves room for an extension to include economic, environmental, and other specific factors.